Transcriptomic Responses to Darkness and the Survival Strategy of the Kelp Saccharina latissima in the Early Polar Night - Li, Huiru; Scheschonk, Lydia; Heinrich, Sandra; Valentin, Klaus; Harms, Lars; Glöckner, Gernot; Corre, Erwan; Bischof, Kai (Frontiers in Marine Science, 2020)
Kelps in the Arctic region are facing challenging natural conditions. They experience over 120 days of darkness during the polar night surviving on storage compounds without conducting photosynthesis. Furthermore, the Arctic is experiencing continuous warming as a consequence of climate change. Such temperature increase may enhance the metabolic activity of kelps, using up storage compounds faster. As the survival strategy of kelps during darkness in the warming Arctic is poorly understood, we studied the physiological and transcriptomic responses of Saccharina latissima, one of the most common kelp species in the Arctic, after a 2-week dark exposure at two temperatures (0 and 4°C) versus the same temperatures under low light conditions. Growth rates were decreased in darkness but remained stable at two temperatures. Pigments had higher values in darkness and at 4°C. Darkness had a greater impact on the transcriptomic performance of S. latissima than increased temperature according to the high numbers of differentially expressed genes between dark and light treatments. Darkness generally repressed the expression of genes coding for glycolysis and metabolite biosynthesis, as well as some energy-demanding processes, such as synthesis of photosynthetic components and transporters. Moreover, increased temperature enhanced these repressions, while the expression of some genes encoding components of the lipid and laminaran catabolism, glyoxylate cycle and signaling were enhanced in darkness. Our study helps to understand the survival strategy of kelp in the early polar night and its potential resilience to the warming Arctic.